Factors related to diabetes prevention and control performance of village health volunteers in Phetchabun Municipality - Khuanpeng, Archaree; Nakju, Saroj; Maton, Thavorn (Journal of Medical and Public Health Region 4, 2026)
This cross-sectional analytical study aimed to examine the diabetes prevention and control practices of village health volunteers (VHVs) in Phetchabun Municipality and to identify factors associated with their performance. The sample consisted of 124 VHVs. Data were collected using a structured questionnaire between January and April 2025. Descriptive statistics, including mean, percentage, and standard deviation, were used for data analysis. The chi-square test and Pearson's correlation coefficient were applied to determine the relationships between variables, with a statistical significance level set at 0.05. The results showed that the overall performance of VHVs in diabetes prevention and control was at a high level ( = 4.24, SD = 0.56). Attitude towards diabetes (r = 0.206, p = 0.022) and social support from public health officers (r = 0.690, p < 0.001) were significantly associated with the VHVs' performance. In contrast, personal factors showed no significant relationship with performance. The findings suggest that enhancing positive attitudes toward diabetes and increasing social support from public health personnel could improve the effectiveness of VHVs in diabetes prevention and control efforts.